(untitled) (Journal of Nuclear Technology in Applied Science, 2024)
In this study traditional microbiological isolation techniques were used to recognize cellulolytic activity of most potent isolates. The iso- Functional studies were carried out to determine the optimum pH, temperature, incubation period, inoculum size, carbon and nitrogen sources for screened isolate. High cellulase producing endophytic bacteria Achromobacter spanius, Bacillus amyloliquefaciens and Stenotrophomonas maltophilia isolated from leaves, stems and roots of; Clover, Wheat, Lettuce, Spinach, Vicia Faba, Garlic, Dill, Olive, Acacia and Prosopis trees were subjected to controlled conditions in laboratory. Tested factors which believed to be effective on improving growth conditions were studied in vitro to achieve the highest production of cellulase enzyme. The highest values of cellulase were produced by Achromobacter spanius (2.50 mg/ml) followed by Bacillus amyloliquefaciens (2.26 mg/ml) after 6 days of incubation. The optimum conditions resulted in optimum cellulase production were 30°C at pH 6 for Achromobacter and Bacillus while the optimum conditions for Stenotrophomonas was 40°C at pH 7. Isolates produced the highest values of cellulase with ammonium sulphate and 30 g/l glucose as nitrogen and carbon sources, respectively. Achromobacter was more effective in producing cellulase than Bacillus and Stenotrophomonas. This was true under all the tested conditions.